Classification and occurrence of an abnormal breathing pattern during cardiopulmonary exercise testing in subjects with persistent symptoms following COVID-19 disease - von Gruenewaldt, A.; Nylander, E.; Hedman, K. (Physiological Reports, 2022)
Reduced exercise capacity and several limiting symptoms during exercise have been reported following severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. From clinical observations, we hypothesized that an abnormal breathing pattern (BrP) during exercise may be common in these patients and related to reduced exercise capacity. We aimed to (a) evaluate a method to classify the BrP as normal/abnormal or borderline in terms of inter-rater agreement; (b) determine the occurrence of an abnormal BrP in patients with post-COVID; and (c) compare characteristics of post-COVID patients with normal and abnormal BrP. In a retrospective, cross-sectional study of patients referred for CPET due to post-COVID April 2020-April 2021, we selected subjects without a history of intensive care and with available medical records. Three raters independently categorized patients` BrP as normal, abnormal, or borderline, using four traditional CPET plots (respiratory exchange ratio, tidal volume over ventilation, ventilatory equivalent for oxygen, and ventilation over time). Out of 20 patients (11 male), 10 were categorized as having a normal, 7 an abnormal, and three a borderline BrP. Inter-rater agreement was good (Fleiss` kappa: 0.66 [0.66-0.67]). Subjects with an abnormal BrP had lower peak ventilation, lower exercise capacity, similar ventilatory efficiency and a similar level of dyspnea at peak exercise, as did subjects with a normal BrP. Patients` BrP was possible to classify with good agreement between observers. A third of patients had an abnormal BrP, associated with lower exercise capacity, which could possibly explain exercise related symptoms in some patients with post-COVID syndrome.